Comparison of the results of modern methods of treatment of elderly women with breast cancer - Abdullayev Habibulla Narzulloyevich; Makhmudova Guljamol Fazliddinovna; Khalikova Feruza Sharopovna (Genius Journals, 2021)
In some tumors, the number of patients older than 70 years is especially high: 86% in prostate cancer, 67-73% in colon cancer, 66-73% in bladder cancer, 61-64% in lung cancer, etc. Despite the obvious urgency of the problem, until recently, the development of rational methods of treatment of elderly patients with malignant tumors has not been given sufficient attention. Surgical intervention remains one of the main methods treatments, and in some cases the only one. The inclusion of radiation therapy in the treatment of breast cancer in the elderly has standard indications and does not differ from those in young patients.
Keywords: Breast cancer; elderly women; surgery; adjuvant therapy